Sedimentary deformation relating to episodic seepage in the last 1.2 million years: a multi-scale seismic study from the Vestnesa Ridge, eastern Fram Strait - Cooke, Frances; Plaza-Faverola, Andreia; Bünz, Stefan; Sultan, Nabil; Ramachandran, Hariharan; Bedle, Heather; Patton, Henry; Singhroha, Sunny; Knies, Jochen (Frontiers in Earth Science, 2023)
Seafloor hydrocarbon seepage is a natural fluid release process that occurs worldwide on continental shelves, slopes, and in deep oceanic basins. The Vestnesa sedimentary ridge in the eastern Fram Strait hosts a deep-water gas hydrate system that became charged with hydrocarbons ∼2.7 Ma and has experienced episodic seepage along the entire ridge until a few thousand years ago, when seepage activity apparently ceased in the west but persisted in the east. Although it has been documented that faults and fractures play a key role in feeding the seeps with thermogenic gases, the mechanisms controlling seepage periodicity remain poorly understood. Here we integrate high-resolution P-cable 3D seismic and Chirp data to investigate the spatial and temporal evolution of high-resolution fractures and fluid flow features in the west of the Vestnesa Ridge. We characterize sediment deformation using a fracture density seismic attribute workflow revealing two highly deformed stratigraphic intervals and associated small-scale pockmarks (<20 m diameter). Chronostratigraphic constraints from the region show that these two highly deformed intervals are influenced by at least three major climatic and oceanic events during the last 1.2 million years: the Mid-Pleistocene Transition (∼1.25–0.7 Ma), the penultimate deglaciation (∼130 ka) and the last deglaciation (Heinrich Stadial 1: ∼16 ka). These periods of deformation appear associated with seismic anomalies potentially correlated with buried methane-derived authigenic carbonate and have been sensitive to shifts in the boundary of the free gas-gas hydrate interface. Our results show shifts (up to ∼30 m) in the depth of the base of the gas hydrate stability zone (GHSZ) associated with major changes in ocean bottom water temperatures. This ocean-driven effect on the base of the GHSZ since the Last Glacial Maximum coincides with the already highly deformed Mid-Pleistocene Transition sedimentary interval and likely enhanced deformation and gas leakage along the ridge. Our results have implications for understanding how glacial cycles impact fracture formation and associated seepage activity.